Current and future LIS competencies - Polona Vilar; Tanja Merčun (Vjesnik Bibliotekara Hrvatske, 2023)
Objective. A study is reported of the perceptions of the Slovenian library practitioners of the competencies needed for their work today and will be needed in the future. Two groups of competencies were considered: generic and professional, the latter in four groups: library management and library operations, library materials and information resources, work with users, organization of knowledge and information.